Synthesis and characterization of poly(acrylamide-co-acrylic acid)grafted poly(styrene-co-methyl methacrylate)microgels via semi batch emulsion polymerization - Ros Azlinawati Ramli, 1980-; Shahrir Hashim, supervisor; Fakulti Kejuruteraan Kimia (2012)
Thesis (Sarjana Sains (Teknologi Polimer)) - Universiti Teknologi Malaysia, 2012